The Role and Threats of Using ChatGPT in Higher Education: Balancing Pedagogical Potential and Ethical Risks - Baiq Mulianah; Fadly Usman; Mauhibur Rokhman; M. Alfin Fatikh; Isni Andriana; Meutia Aisyah Nabila; Mohammad Maulana Nur Kholis (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
The increasing use of generative AI tools in education highlights the need to understand how they can be effectively integrated into university-level teaching and learning. Although these tools offer great promise, the absence of a transparent and ethical framework for their implementation poses real challenges in aligning them with curriculum goals. AI technologies, such as ChatGPT, have already begun to reshape the way students learn, particularly in higher education settings. This research examines how students utilize ChatGPT for academic purposes, including studying, research, and learning activities. Using a quantitative approach, the study identifies usage trends and finds that students generally feel confident using ChatGPT, with many reporting improved engagement and productivity. The lack of regulated ethical standards for ChatGPT use and lecturer interventions prohibiting irresponsible use also impact the widespread use of ChatGPT in higher education settings. This study used quantitative data analysis involving 415 students from four universities: KH Abdul Chalim University, Brawijaya University, Sriwijaya University, and Gadjah Mada University. This research examines the benefits, challenges, and ethical considerations of utilising AI-based software in academic settings, particularly in higher education.